Feeding interval and use of donor breast milk for very low birthweight infants: A nationwide survey in Japan - Mariko Ashina; Kazumichi Fujioka; Satsuki Totsu; Hiromichi Shoji; Tokuo Miyazawa; Kazuko Wada; Kazumoto Iijima; Ichiro Morioka (Pediatrics and Neonatology, 2019)
Background: Enteral feeding is critical for postnatal growth of very low birthweight infants (VLBWI); however, a standard feeding strategy has not been established in Japan. A 2- or 3-h feeding interval is generally used, but no clear evidence supports either approach. Additionally, there is no nationwide breast milk bank in Japan and no consensus exists on the use of donor breast milk (DBM). To clarify the current feeding strategies for VLBWI in Japan, we undertook a nationwide survey. Methods: We sent a questionnaire to the 382 NICUs included in the Neonatal Research Network in Japan. We sought information on NICU size, number of admissions, necrotizing enterocolitis (NEC) incidence, feeding interval, and use of DBM. Results: We received responses from 217 NICUs (56.8%), including 76 tertiary centers and 140 regional centers. We only analyzed data obtained from tertiary perinatal centers with a high response rate (77.6%) owing to the insufficient response rate of lower-level facilities (<50%). Most NICUs (71.1%) used a 3-h feeding interval. Only 9.2% used a 2-h interval for all VLBWI. Most NICUs (64.5%) never used DBM, which is not routinely pasteurized. DBM was used in 27 NICUs (35.5%), with and without limitations. Data from 14,233 VLBWI were analyzed; 258 infants (1.8%) were diagnosed with NEC from 2011 to 2015. The incidence of NEC was higher in NICUs that used a 2-h interval (2.7%) than in others. No association was found between NEC and the use of DBM. The NEC incidence did not differ between centers using the most common strategy of a 3-h interval without DBM and those using other strategies. Conclusion: Most NICUs in Japan use a 3-h feeding interval and do not use DBM for VLBWI. Further prospective studies including multiple confounders are required to clarify the relationship between feeding strategy and the incidence of NEC. Key Words: donor breast milk, enteral feeding, feeding interval, nationwide survey, very low birth weight infants